Pengaruh Bauran Pemasaran terhadapkeputusan Membeli Tiket Pesawat di Total Nusa Indonesia Tour And Travel Yogyakarta - I Putu Hardani Hesti Duari (Media Wisata, 2014)
The marketing mix is one of the important things to increase and develop a unit business. In this conceptual paper attempt, the marketing mix can make a good effect by the customer decides to buy a domestic ticket. In the tourism industry especially the services industry that marketing mix is known as 7P. It includes product, place, price, promotion, people, process and physical evidence. 7p of the Marketing Mix here took place at PT. Total Nusa Indonesia Tour & Travel Agencies in Yogyakarta headquarters. The total respondents are 100 respondents with quantitative analysis of data. Through the overall Uji F is known that the marketing mix significantly influences the decision to buy a plane ticket at PT Total Nusa Indonesia Tour & Travel in Jogjakarta. And the product is the biggest decision to make the decision to buy a plane ticket. This can occur due to variations in domestic flight ticket complete product. Then follow by the other marketing mix component.